Teaching English in rural area: Challenge and Hope for The future - muhammad fathur rohman; ATIKA DYAH ANDRIASIWI ANDRIASIWI; NAILY HUBBATUL KAROMAH; REFASURYA RIDHO NURYANDHI; Octha Ika Rahmawati; Ima Isnaini Taufiqur Rohmah; Eline Rozaliya Winarto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2022)
The purpose of this study was to look into the challenges that English teachers face when teaching English in rural junior high schools in Balen, as well as the strategies they use to overcome those challenges. This study used semi-structured interviews and classroom observation to find out the answers. The study's participants were five English teachers from five rural junior high schools in Balen Bojonegoro. The study captured the perspectives of English teachers. The findings revealed five challenges that English teachers face when teaching English in rural high schools. Students' competence, students' motivation, teaching media, teacher development, an insufficient number of teachers, and parental support were the seven challenges in teaching English. As a result, the English teachers employed four strategies to deal with these challenges. These four teaching strategies included using a variety of teaching methods and techniques, matching students' levels and learning situations, collaborating with schools and parents, and encouraging students' motivation. Finally, it is hoped that the findings of this study will assist English teachers in discovering teaching strategies that are appropriate for the challenges they faced